Analisis Faktor-faktor yang Memengaruhi Penggunaan Internet Banking di Jabodetabek - Bani Saad (STIE Indonesia Banking School, 2017)
Internet banking service allows customers to conduct banking transactions online via a bank’s website, anytime, anywhere, faster, and relatively lower cost compared to other physical media services. According to that condition, the researcher was motivated to analyze the influence of some factors that affect customer acceptance of Internet Banking in Jabodetabek, using the framework of Technology Acceptance Model (TAM) based on Pikkarainen et al. (2004). Some variables analyzed in this research are Perceived usefulness (PU), Perceived ease of use (PEoU), Perceived Enjoyment (PE), Information on Internet Banking (I), Security and Privacy (SP), Quality of internet connection (Q), & internet banking use (U). The respondents of this research are Bank customers in Jabodetabek who use Internet Banking. Based on the data analysis, only information on internet banking has a positive and significant effect on internet banking use, Other independent variable doesn’t have a significant effect on internet banking use.